Intravenous versus inhalational anaesthesia and lung ventilation–perfusion matching. Issue 3 (May 2019) - Peyton, Philip J; Marsh, Harry; Thompson, Bruce R
Lung gas exchange efficiency deteriorates during general anaesthesia due to ventilation–perfusion ( V/Q ) scatter. Propofol total intravenous anaesthesia (TIVA) may preserve V/Q matching better than inhalational agents. We compared V/Q matching in patients randomized to either TIVA or sevoflurane anaesthesia, using deadspace and shunt measurements and the MIGET (Multiple Inert Gas Elimination Technique). Baseline arterial blood and mixed expired gas sampling was done before induction and repeated after one to two hours of relaxant general anaesthesia in 20 patients, supine with controlled ventilation at an FiO2 of 0.3 and a target end-tidal PCO2 of 30–35 mmHg. Blood samples for MIGET were processed after headspace equilibration by gas chromatography. The primary endpoint was a comparison of the two groups in the change from baseline of absolute difference between log standard deviation of ventilation and blood flow distributions (∂(σV −σQ )). Deadspace fraction increased and PaO2 /FiO2 ratio decreased across both groups overall with anaesthesia, but change in deadspace was not different between groups (mean (standard deviation, SD) sevoflurane 21.8% (11.7%) versus TIVA 20.5% (10.6%), P = 0.601). Change in PaO2 /FiO2 ratio was also similar between groups (mean (SD) sevoflurane −51.9 (69.1) mmHg versus TIVA −78.3 (76.9) mmHg, P = 0.43), as was change in shunt fraction (δQs/Qt mean (SD) sevoflurane −5.1% (12.6%) versus TIVA 0.4% (7.7%), P = 0.174). The primary endpoint ∂(σV −σQ ) was not different between sevoflurane and propofol TIVA groups (mean (SD) 0.17 (0.81) versus 0.17 (0.29), P = 0.94). TIVA did not better preserve V/Q matching in patients undergoing anaesthesia with controlled ventilation compared with sevoflurane.